2012
DOI: 10.1002/gcc.22003
|View full text |Cite
|
Sign up to set email alerts
|

Survey of 548 oncogenic fusion transcripts in thyroid tumors supports the importance of the already established thyroid fusions genes

Abstract: Neoplasms frequently present structural chromosomal aberrations that can alter the level of expression of a protein or to the expression of an aberrant chimeric protein. In the thyroid, the PAX8-PPARG fusion is present in the neoplastic lesions that have a follicular architecture-follicular thyroid carcinoma (FTC) and follicular variant of papillary thyroid carcinoma (FVPTC), and less frequently in follicular thyroid adenoma (FTA), while the presence of RET/PTC fusions are largely restricted to papillary thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…RET proto-oncogene fusions have been identified previously in both lung adenocarcinoma414 and thyroid cancer15. Consistent with these studies, we observed recurrent CCDC6 – RET fusions in thyroid cancer15 but also identified several RET fusions with novel partners, including AKAP13 , FKBP15 , SPECC1L and TBL1XR1 (Fig.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…RET proto-oncogene fusions have been identified previously in both lung adenocarcinoma414 and thyroid cancer15. Consistent with these studies, we observed recurrent CCDC6 – RET fusions in thyroid cancer15 but also identified several RET fusions with novel partners, including AKAP13 , FKBP15 , SPECC1L and TBL1XR1 (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Consistent with these studies, we observed recurrent CCDC6 – RET fusions in thyroid cancer15 but also identified several RET fusions with novel partners, including AKAP13 , FKBP15 , SPECC1L and TBL1XR1 (Fig. 1, Supplementary Fig.…”
Section: Resultssupporting
confidence: 87%
“…RNA-seq has spurred important gene fusion discoveries for a number of different cancers, including lung [6, 7], prostate [3, 8, 9], breast [1012], brain [13], thyroid [14] and bladder carcinomas [15]. One obvious benefit from gene fusion discovery is the potential to develop novel treatments that target these genetic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Actually, modern RNA-sequencing technologies have provided us with thousands of RNA chimeras 14 . A tiny number of them are known to be transcribed from fusion genes that are formed due to genetic alterations, such as chromosomal translocation and genomic DNA deletion or amplification 9 . Unfortunately, the vast remaining majority, i.e., those not associated with a known genomic alteration, remain putative and are not very meaningful to us so far, because their existence has not been verified with a vigorous method and because their full-length sequence has not been cloned and, thus, their open reading frame is unclear 16 .…”
Section: Introductionmentioning
confidence: 99%